2021
DOI: 10.1007/s10608-021-10207-7
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity Moderates the Impact of COVID-19 Perceived Stress on Anxiety and Functional Impairment

Abstract: Background The COVID-19 pandemic has had a profound negative impact on mental health symptoms and daily life functioning across the United States and worldwide. Past work has revealed that perceived stress relates to poorer outcomes, however, little work to date has examined factors that may exacerbate these outcomes, and no work to date has examined this relation in terms of COVID-19. Anxiety sensitivity is a promising individual difference factor that has shown to be related to mental health and functional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Perceived stress can affect people’s mental health in different ways [ 14 ]: it is a person’s ability to interpret life events as overwhelming, erratic, or uncontrollable. Perceived stress during the COVID-19 pandemic emphasizes the extent to which an individual believes he or she has control over unexpected or difficult events or emotions arising from the situation (illness, isolation, and/or financial problems) [ 15 ]. Duration of measures, frustration, fatigue, inadequate information, economic problems, fear of contagion, media reports, etc., are considered as stressors that increase the stress perceived by individuals [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perceived stress can affect people’s mental health in different ways [ 14 ]: it is a person’s ability to interpret life events as overwhelming, erratic, or uncontrollable. Perceived stress during the COVID-19 pandemic emphasizes the extent to which an individual believes he or she has control over unexpected or difficult events or emotions arising from the situation (illness, isolation, and/or financial problems) [ 15 ]. Duration of measures, frustration, fatigue, inadequate information, economic problems, fear of contagion, media reports, etc., are considered as stressors that increase the stress perceived by individuals [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that anxiety sensitivity might intensify the experience of threat during the pandemic, resulting in a fear of contamination and compulsive hygiene checks (Taylor et al, 2020 ). Stress stemming from COVID-19 has been found to be associated with a greater likelihood of clinically significant anxious arousal symptom severity and global anxiety symptom severity at higher levels of anxiety sensitivity (Manning et al, 2021 ). Furthermore, research has found associations between anxiety sensitivity and PTSD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…People with high anxiety sensitivity perceive harmless bodily stimuli as “dangerous,” therefore anxiety sensitivity was determined as a predictor of the fear of COVID‐19 (Taylor et al, 2007 ; Waqas et al, 2020 ). As far as we could detect, analysis of the relationship between anxiety sensitivity and fear of COVID‐19 is limited to a total of seven studies (Baiano et al, 2020 ; Malesza & Kaczmarek, 2021 ; Manning et al, 2021 ; Rogers et al, 2021 ; Sadeghzadeh et al, 2021 ; Waqas et al, 2020 ; Xia et al, 2021 ). Of these, three were performed on university students (Baiano et al, 2020 ; Sadeghzadeh et al, 2021 ; Waqas et al, 2020 ), three on the general population (Malesza & Kaczmarek, 2021 ; Manning et al, 2021 ; Rogers et al, 2021 ), and one on healthcare workers (Xia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we could detect, analysis of the relationship between anxiety sensitivity and fear of COVID‐19 is limited to a total of seven studies (Baiano et al, 2020 ; Malesza & Kaczmarek, 2021 ; Manning et al, 2021 ; Rogers et al, 2021 ; Sadeghzadeh et al, 2021 ; Waqas et al, 2020 ; Xia et al, 2021 ). Of these, three were performed on university students (Baiano et al, 2020 ; Sadeghzadeh et al, 2021 ; Waqas et al, 2020 ), three on the general population (Malesza & Kaczmarek, 2021 ; Manning et al, 2021 ; Rogers et al, 2021 ), and one on healthcare workers (Xia et al, 2021 ). Anxiety sensitivity in the physical field was declared as an important predictor of the fear of COVID‐19 (Waqas et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%